Willingness to accept for municipal waste recycling: A case study from Lima, Peru - Mougenot, Benoît (2017)
Waste management seems to be a wide challenge for cities in developing countries. Resource constraints and inefficient institutions inevitably call for labour from the informal sector in this activity. We employ the contingent valuation method and a logit model to estimate recyclers’ Willingness To Accept (WTA) to participate in recycling household’s waste in Lima (la Victoria District). We examine various aspects, including socioeconomics factors, awareness and recycling activity. The required WTA estimate is 1,355.86 Soles (USD 413.13), higher than both the minimum living wage fixed at 750 Soles and the monthly per capita productivity of recyclers, calculated at 986.05 Soles (USD 300.45), using a market prices method in the latter. The economic value of solid waste finance more than 70 percent of the recyclers’ monthly willingness to accept, considering recyclers productivity. Although this is a promising outcome, there is a need for further research on the effects of education, attitudes, and awareness of solid waste management from both the public and private sectors. © 2017 International Business Information Management Association IBIMA.